Beyond Documentation: Understanding Implementation Barriers of Halal Certification Among Micro and Small Enterprises - Ariska, Nenda; Elwardah, Khairiah; Zaki, Khozin; Yustati, Herlina; Novita Sari, Kiki (Institut Agama Islam Negeri Kendari, 2024)
This study examines the multifaceted challenges faced by Micro and Small Enterprises (MSEs) in implementing halal certification in Selebar District, Bengkulu City, Indonesia. Despite the mandatory halal certification requirement established by Law Number 33 of 2014, many MSEs have yet to comply with this regulation. Through qualitative field research involving in-depth interviews with 11 MSE owners, this study identifies three critical barriers to halal certification implementation. First, there is a significant knowledge gap among MSE actors regarding halal certification requirements and available support programs, particularly the government's free certification initiative (SEHATI). Second, MSEs face substantial documentation challenges, with none of the studied businesses possessing the required Business Identification Number (NIB), compounded by limited technological literacy that hinders the application process. Third, there is low awareness among MSE actors about the strategic importance of halal certification for business sustainability. The findings suggest that successful implementation of halal certification requires a comprehensive approach that addresses knowledge barriers, simplifies documentation requirements, and builds awareness through targeted education programs. This research contributes to understanding the practical challenges of implementing halal regulations at the micro-enterprise level and offers policy recommendations for improving certification adoption rates.